1929 Tenn. Priv. Acts 2018, vol. 2, An Act to Amend . . . an Act Entitled an Act to Incorporate the Town of Lebanon in the County of Wilson, State of Tennessee . . . , ch. 685, art. 2, § 1, pt. 38. - (:unkn) unknown (My University, 1929)
[T]o regulate or prevent the discharging, firing, shooting, or carrying of guns, pistols and fireworks in the City.
Keywords: CARRY; DISCHARGE